Disambiguating the Concept and Application of Islamic Law to the Civil Procedure and Adjudication - Mohsen Kazemi; Bahram Taqipour; Alireza Salehifar (آموزه‌‌های فقه مدني)
The function and the concept of law in trials and adjudication has ambiguity. Based on the soul and the evolutionary process of law, the intent of Sharia (Arabic: شرع Islamic law) in the current rules is an independent concept from law, public order and good morality (desired virtuous values) but sometimes this term in the rules has not been used right (accurate). From functioning aspect, after realizing the illicitness of the claim (case), it should not be trusted in the appearance of law i.e. Article 89 of civil procedure code of Iran indicating issuing the abatement. Also referring to the Islamic law from both parties, court of appeal and supreme court of Iran in appealing to the initial judgment limits to the decisions that issuing of the initial decision depends on the silence of law and with referring to Islamic law has been issued. The ambiguity originated from the concept of Sharia (شرع) in the rules, it is possible to study in the area of the adjudication. In this paper it has been surveyed the duty of the adjudicator to the Islamic law and the duty of the court on adjudicating the appeal against the decision of the court (dispute) from the point of view of being in contrast to the Islamic law principles.